PEMANFAATAN RESIN Ca-ALGINAT TERMODIFIKASI DENGAN ETILENA DIAMINENA TETRAASETAT (EDTA) DALAM TAHAPAN PRAKONSENTRASI ION Mn(II) BERBASIS METODE KOLOM - Sari, Rahma Juwita; Panggabean, Aman Sentosa; -, Erwin (Jurusan Kimia FMIPA UNMUL, 2016)
Research on modification of Ca-Alginate microcapsules with Ethylene Diamin Tetra Acetate (EDTA) and Utilization in stages pre concentration column Ion Pb based method has been done. Pre concentration method Pb metal ions is done by using the column or Off-Line method, the water sample is inserted into the column, in the elution using 1.5 M HCl, then eluat were collected and measured using Atomic Absorption Spectrophotometer. The optimum conditions in resin manufacture Ca-Alginate-EDTA is on the composition of CaCl2 1 M Na-alginate 1%, and 0.75% EDTA. The optimum conditions analytical performance of this resin microcapsules with the absorption of Pb most best at pH 8, retention capacity of 0.6546 mg / g resin, 1.5 M HCl eluent The concentration by volume Pb is 8 mL and 3 mL HCl eluen volume, analytical performance of this method good enough for Pb ion analysis is shown of the measurement value detection limit of 0.0469 mg / L level to able replicates expressed as a percentage coefficient of variance for 1:20%. this method can be applied to the analysis of metal ions Fe in water samples from the environment to the value of recoveries of> 95%, using techniques spike indicates that the sample matrix derived from Karang Mumus River and Well Water does not affect the measurement results and can be used by analysis of Pb in the sample water at trace levels. Keywords: Preconcentration, Resin Ca-Alginate-EDTA, Pb, Spectrophotometer